Exploring the Role of Microbial Communities in the Formation and Fossilization of Coal Deposits from West Bengal Mines - Dey, Sreedeep; Das, Sreejita (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
This study investigates the crucial function of microbial populations in coal formation in West Bengal, India, specifically the Raniganj and Jharia coalfields. We used metagenomic analysis, isotopic research, and experimental simulations to investigate the role of ancient and present microbes to coalification. Key findings demonstrated that anaerobic bacteria such as Clostridium spp. and Desulfovibrio spp., as well as methanogenic archaea, enhanced organic matter decomposition and mineralization. Isotopic studies revealed microbial activity in carbon cycling and sulfate reduction, with δ13C depletion and δ34S enrichment. Experimental simulations reproduced coal-like material production, underlining the importance of microorganisms in coal preservation. This study sheds light on microbial-geochemical interactions and proposes potential biotechnological applications in energy production and carbon sequestration.